The Decline and Disappearance of Chipped-Stone Tools: New Insights From Qubur el-Walaydah, a Late Bronze/Iron Age Site in Israel. (3rd April 2018) - Manclossi, Francesca; Rosen, Steven A.; Lehmann, Gunnar
ABSTRACT: Technological analyses of the lithic assemblage recovered from the excavations at Qubur el-Walaydah offer new insights into the nature of the specialized production system of sickle blades during the Late Bronze-Iron Age, and provide new data sets concerning the decline of chipped-stone technologies. Although the knapping technology used for the production of flint sickle segments was relatively simple, the spatial distribution of this system, the hafting procedures, and other technological considerations suggest that the specialists were no longer solely flint knappers, but had become sickle artisans. They produced the complete sickles that the farmers, who in turn lost their role in the manufacturing process, used. This specialized system can be characterized as a kind of vertical production integration. The organization of the production of flint sickles, moreover, may offer insights on the last stage of the stone-metal replacement process. If the intrinsic properties of iron and its availability must have played an important role, the flint-iron substitution might be facilitated by the fact that the production system was already characterized by a form of specialization where the users of these objects were no longer the producers. In this regard, the simultaneous fall of ad hoc flint tools represent another facet of the same phenomenon. If within the lithic production system the manufacture of sickles and ad hoc tools represent two distinct sub-systems, the large-scale adoption of iron implements suggests the emergence of a single specialized system producing different types of cutting tools, then used for different tasks. Thus, the end of chipped stone tools is related not only to the efficiency of iron implements, but also to a structural change in the relationship between tool consumers and producers.